Indigenous Birth as Ceremony and a Human Right - Ashley Hayward; Jaime Cidro (Harvard FXB Center for Health and Human Rights, 2020)
Birthing can be an empowering experience for women. Within many Indigenous cultures around the world, birth is a ceremony to celebrate new life, acknowledging the passing from the spiritual world into the physical world. While initiatives to "indigenize" health care have been made, this paper argues that the United Nations Declaration on the Rights of Indigenous Peoples and the United Nations Sustainable Development Goals contain frameworks for Indigenous rights that include the right to incorporate Indigenous childbirth ceremonies into clinical practice. Examining the importance of birthplace, this paper details a current movement in Manitoba, Canada, to "bring birth home," which recognizes that the determinants of health experienced in the early stages of a child's development can have health implications for an individual's future.